Seasonal Concentrations of Insecticide Residues, Ecological and Health Risks of Waters from Déganobo Lake System in San-Pedro, Cote D'Ivoire - K. F. A. Konan; M. K. Yao (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to evaluate the seasonal concentrations of insecticide residues, ecological and health risks of waters from Déganobo Lake System in San-Pedro, Cote D' Ivoire using appropriate standard methods. For this study, waters samples from this aquatic ecosystem were collected over a year (from August 2022 to July 2023). The concentrations of these insecticide residues were obtained according to the MA. 403-Pest 3.1 standard (CEAEQ, 2011) with minor modifications. Generally, the seasonal concentrations of these residues were significant in these waters, especially those of methyl parathion, except for acetamiprid and deltamethrin, which were undetectable throughout the study period. This situation is related to their extensive use in agricultural practices in the watershed of this aquatic ecosystem. Most of these insecticide residues showed high concentrations in these waters during the small and great dry seasons, while their lowest concentrations were observed during the small rainy season. This high presence of insecticide residues in these waters presents significant ecological and health risks, particularly due to the residues of bifenthrin, chlorfenvinphos, ethyl parathion, methyl parathion, and vinclozolin. This study highlights the need to implement effective management practices to safeguard and protect this lake system to ensure its impressive biodiversity in the long term.